Creatine supplementation: a novel role in antioxidant system in exercise and in chronic diseases - Stefani, Giuseppe Potrick; Nunes, Ramiro Barcos; Rhoden, Claudia Ramos (Revista Contexto & Saúde, 2015)
The effects of creatine supplementation related to ergogenic action which increases maximum strength and body mass has been extensively revised. In the least years it has been hypothesized a novel function of creatine as antioxidant agent. There are few data of this amine on oxidative stress and its role in antioxidant system. A small amount of studies in vitro and in vivo showed promising results related to indirect antioxidant effect, which evaluated the isolated supplementation protocols or added to standard diet. Creatine supplementation seems to exert positive effect on health, mainly in exercise conditions due to the ergogenic action. Furthermore, some evidences suggest that the supplementation might have positive effects on energy metabolism and functional capacity in chronic degenerative diseases. Expressive results were observed in Parkinson's disease and Huntington's disease, in which the creatine might acts as neuroprotective agent, neutralizing the reactive oxygen and nitrogen species action. The modulation of mitochondrial creatine kinase seems to play an important role in reactive oxygen species production, such as radical anion superoxide. This review aims to show the scientific evidences about antioxidant effect of creatine supplementation, when utilized alone or associated with physical exercise, in health individuals and in patients with chronic degenerative diseases.